A functional role for both γ‐aminobutyric acid (GABA) transporter‐1 and GABA transporter‐3 in the modulation of extracellular GABA and GABAergic tonic conductances in the rat hippocampus. (8th March 2013) - Kersanté, Flavie; Rowley, Samuel C. S.; Pavlov, Ivan; Gutièrrez‐Mecinas, María; Semyanov, Alexey; Reul, Johannes M. H. M.; Walker, Matthew C.; Linthorst, Astrid C. E.
Key points:   The extracellular concentration of the neurotransmitter γ‐aminobutyric acid (GABA) is critical in determining GABAA receptor‐mediated tonic conductance in the hippocampus.   Two GABA transporters (GAT‐1 and GAT‐3) are present in the CA3 and dentate gyrus of the hippocampus. The expression of GAT‐3 is confined to astrocytes and its role in the regulation of GABAergic neurotransmission is unclear.   Using microdialysis and specific GAT uptake inhibitors we show that not only GAT‐1 but also GAT‐3 contributes to the regulation of hippocampal extracellular concentrations of GABA in rats under in vivo conditions.   We further found that changes in extracellular concentrations of GABA resulting from both GAT‐1 and GAT‐3 inhibition precipitate supra‐additive changes in tonic conductance in dentate granule cells in vitro .   These results help us to understand the mechanisms underlying the regulation of GABAergic tonic conductance in the hippocampus and can help to develop improved therapeutic strategies for neurological and psychiatric disorders. Abstract  Tonic γ‐aminobutyric acid (GABA)A receptor‐mediated signalling controls neuronal network excitability in the hippocampus. Although the extracellular concentration of GABA (e[GABA]) is critical in determining tonic conductances, knowledge on how e[GABA] is regulated by different GABA transporters (GATs) in vivo is limited. Therefore, we studied the role of GATs in the regulation of hippocampal e[GABA] using in vivo microdialysis in freely moving rats. Here we show that GAT‐1, which is predominantly presynaptically located, is the major GABA transporter under baseline, quiescent conditions. Furthermore, a significant contribution of GAT‐3 in regulating e[GABA] was revealed by administration of the GAT‐3 inhibitor SNAP‐5114 during simultaneous blockade of GAT‐1 by NNC‐711. Thus, the GABA transporting activity of GAT‐3 (the expression of which is confined to astrocytes) is apparent under conditions in which GAT‐1 is blocked. However, sustained neuronal activation by K + ‐induced depolarization caused a profound spillover of GABA into the extrasynaptic space and this increase in e[GABA] was significantly potentiated by sole blockade of GAT‐3 (i.e. even when uptake of GAT‐1 is intact). Furthermore, experiments using tetrodotoxin to block action potentials revealed that GAT‐3 regulates extrasynaptic GABA levels from action potential‐independent sources when GAT‐1 is blocked. Importantly, changes in e[GABA] resulting from both GAT‐1 and GAT‐3 inhibition directly precipitate changes in tonic conductances in dentate granule cells as measured by whole‐cell patch‐clamp recording. Thus, astrocytic GAT‐3 contributes to the regulation of e[GABA] in the hippocampus in vivo and may play an important role in controlling the excitability of hippocampal cells when network activity is increased.